Low Threshold Polariton Lasing from a Solution‐Processed Organic Semiconductor in a Planar Microcavity. Issue 12 (15th April 2019) - Rajendran, Sai Kiran; Wei, Mengjie; Ohadi, Hamid; Ruseckas, Arvydas; Turnbull, Graham A.; Samuel, Ifor D. W.
Abstract: Organic semiconductor materials are widely studied for light emission and lasing due to their ability to tune the emission wavelength through chemical structural modification and their relative ease of fabrication. Strong light–matter coupling is a promising route toward a coherent light source because it has the potential for polariton lasing without population inversion. However, the materials studied so far have relatively high thresholds for polariton lasing. Here, the suitability of pentafluorene for strong coupling and low threshold polariton lasing is reported. A protective buffer layer is used to reduce degradation during fabrication and the lasing threshold is lowered using negative detuning to maximize radiative decay. A low threshold of 17 µJ cm −2, corresponding to an absorbed energy density of 11.7 µJ cm −2, is obtained. This study shows that pentafluorene is an attractive material for polariton lasing and will assist in the development of low threshold electrically pumped lasing from polariton devices. Abstract : Strong light–matter coupling is a promising route towards coherent light sources. The authors show that pentafluorene is an attractive material for strong light–matter coupling and low threshold polariton lasing. A low threshold of 17 μJ cm −2 is obtained by optimum material and dielectric microcavity design. This study will assist the development of low threshold electrically pumped polariton lasing devices.